Pemanfaatan Zakat untuk Meningkatkan Pendapatan Mustahiq pada BAZNAS Kabupaten Dharmasraya - Tezi Asmadia; Ihdi Aini; Netta Agusti (ZAWA: Management of Zakat and Waqf Journal, 2023)
The main problem in this study is that the Productive Economy program is one of the Dharmasraya Makmur programs which aims to increase mustahiq's income in the long term and change their economic capabilities for the better. However, in carrying out productive zakat distribution programs, many problems occur in the field, including failures due to their own efforts such as production aspects, low business motivation, indiscipline in the use of zakat funds and indiscipline in the use of funds, causing differences in the income of mustahiq recipients of productive zakat funds. The type of research conducted is field research or field research using a descriptive qualitative approach. Data collection techniques that the authors use are interviews and documentation. The analysis technique used is data reduction, data presentation, and drawing conclusions. The results showed that the distribution of productive zakat funds in the form of business capital provided by BAZNAS Dharmasraya Regency to 30 mustahiq people as a sample of this study can be said to be successful in increasing mustahiq income in terms of the average increase in mustahiq income, which is 80%. However, mustahiq who are not successful in developing their business because these funds are used to meet mustahiq's personal needs and productive zakat funds channeled by BAZNAS Dharmasraya Regency are quite large but not accompanied by coaching because the accompanying HR (Human Resources) is lacking, so mustahiq who receive these funds are trying to develop their own business, but in the middle of running the business, they are confused about how to manage the business that is being occupied so that there is no significant development.